Accuracy of end-on fluoroscopy in predicting implant position in relation to the vertebral canal in dogs - Goffart, Laura M.; Precht, Christina; Fosgate, Geoffrey T.; Maiolini, Arianna; Hettlich, Bianca F. (Frontiers in Veterinary Science, 2022)
Objective: To evaluate the accuracy of end-on fluoroscopy in predicting implant position in relation to the vertebral canal in the canine thoracolumbar vertebral column. Study design: In vitro imaging and anatomic study. Animals: Canine cadaveric thoracolumbar vertebral columns (n = 5). Methods: Smooth Steinmann pins were inserted bicortically into the thoracolumbar vertebral columns between T10 and L7 using recommended insertion angles. Penetration of the spinal canal was not strictly avoided. After pin placement, end-on fluoroscopy images were obtained of each pin. Pin position was subsequently assessed by four evaluators and determined to either being out of the vertebral canal or in, with the latter being additionally divided into partially or completely penetrating the canal. To assess potential differences in modalities, fluoroscopy images were grey-scale inverted and evaluated again later by the same four individuals. Correct identification of pin position in relationship to the vertebral canal was assessed for both fluoroscopy images. Anatomic preparation of the spines was used for verification of pin position in relation to the spinal canal. Data from this study were compared with historical data on accuracy using plain radiography and computed tomography (CT). Results: The overall accuracy of end-on fluoroscopy (F) and inverted fluoroscopy (Fi) were statistical better than conventional radiographic assessment (p < 0.001). Overall sensitivity and specificity of F to detect vertebral canal penetration was 98.8 % (95% confidence interval (CI), 96.0 - 99.6) and 98.0% (95% CI, 77.0 - 99.9), respectively. For Fi, sensitivity and specificity were 97.0% (95% CI, 91.5 - 99.0) and 98.5% (95% CI, 81.5 - 99.9) respectively. F exceeded Fi for the sensitivity of detecting pin penetration into the vertebral canal (p = 0.039) but specificities were not different (p = 0.585). Conclusion: Just as CT, end-on fluoroscopy outperforms radiographic assessment of pin position in relationship to the thoracolumbar spinal canal in cadaveric dogs. Clinical Significance: End-on fluoroscopy, with or without inversion, is accurate in identifying vertebral canal violation by bicortically placed Steinmann pins. When CT is not available, end-on fluoroscopy might be a valuable imaging modality to determine pin position in the canine vertebral column.